Faktor-Faktor yang Mempengaruhi Pengguna Napza Suntik dalam Tindakan Pemanfaatan Layanan Program Terapi Rumatan Methadon (PTRM) di Kota Cirebon - Dessy Aryanti; Bagoes Widjanarko; Kusyogo Cahyo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2016)
ABSTRACTAccording to the risk factors as a result of injecting drug use (IDU) were second highest, after the heterosexual and homo-bisexual. In IDUs face two risks for contracting HIV / AIDS, from the use of unsterilized needles and performed together or alternately with other IDUs and also through sexual intercourse, especially that done with more than one partner without using a condom. Methadone maintenance treatment program (PTRM) is included in the Harm Reduction program – This is a program of harm reduction drug use in preventing transmission of HIV / AIDS. This research is quantitative with correlational design, sampling using the technique across sectional the total population 50 person IDUs of injecting drug users in the city of Cirebon -use structured questionnaires technique. From the 50 IDUs who were respondents in this research note that 68% did not use PTRM services. It is because most IDUs still can not stop using injection drugs and have not been willing to switch to PTRM. Results of univariate analysis to determine the level of knowledge of IDUs about PTRM 88% have a good category, the attitude of the respondents 80% have category support PTRM, family attitudes 50% have category support PTRM, attitudes of peers 72% have a category does not support the utilizations PTRM, attitude of health workers 66% category does not support PTRM, and the availability of facilities and health facilities 52% support in PTRM services. For the bivariate analysis showed that the attitude of IDUs to program substitution therapy methadone-related measures the utilization of PTRM, whereas knowledge factors, family attitudes, attitudes of peers, attitude of health workers, and the availability of facilities. Then knowledge of IDUs about PTRM shows no relationship with the actions the utilization of PTRM , And based on multivariate analysis known that the action the utilization of PTRM is influenced by the family attitudes were supportive of the utilizations of Methadone maintenance treatment program (PTRM).Keywords: drug, injection, PTRM, HIV/AIDS